New Avian tracks from the lower to middle Eocene at Fossil Hill, King George Island, Antarctica - Mansilla, Héctor G.; de Valais, Silvina; Stinnesbeck, Wolfgang; Varela, Natalia A.; Leppe, Marcelo A. (Antarctic Science)
Trace fossils are long known to exist in the Fossil Hill Formation (lower to middle Eocene) at Fildes Peninsula, King George Island, Antarctica. During fieldwork in 2009, abundant new avian tracks were recovered, which are analysed here. Three avian ichnotaxa are distinguished. The most common impressions are tridactyls and tetradactyls with slender digit imprints II–IV and a posterior hallux. They are included in the ichnogenus Gruipeda. In addition tridactyl and tetradactyl footprints with short and thick digit impressions are conferred to Uhangrichnus. The third ichnotaxon is a tridactyl impression with broad and short digits assigned to Avipeda. The latter taxon is here documented for the first time from Antarctica. These avian tracks are preserved in volcaniclastic sediments consisting in reddish-brown layers of mudstone intercalated with coarse sandstone. The sequence represents lacustrine environments which seasonally dried and were episodically refilled. Fil: Mansilla, Héctor G. Instituto Antártico Chileno. Laboratorio de Palaeobiología; Chile Fil: de Valais, Silvina. Universidad Nacional de Rio Negro. Sede Alto Valle. Instituto de Investigaciones en Paleobiologia y Geologia; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Stinnesbeck, Wolfgang. Universität Heidelberg. Institut für Geowissenschaften; Alemania Fil: Varela, Natalia A. Instituto Antártico Chileno. Laboratorio de Palaeobiología; Chile Fil: Leppe, Marcelo A. Instituto Antártico Chileno. Laboratorio de Palaeobiología; Chile